2003
DOI: 10.1074/jbc.m303221200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Codes within the Family of Mammalian Phox and Bem1p Domain-containing Proteins

Abstract: The Phox and Bem1p (PB1) domain constitutes a recently recognized protein-protein interaction domain found in the atypical protein kinase C (aPKC) isoenzymes, /-and PKC; members of mitogen-activated protein kinase (MAPK) modules like MEK5, MEKK2, and MEKK3; and in several scaffold proteins involved in cellular signaling. Among the last group, p62 and Par6 (partitioning-defective 6) are involved in coupling the aPKCs to signaling pathways involved in cell survival, growth control, and cell polarity. By mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
388
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(416 citation statements)
references
References 51 publications
19
388
1
Order By: Relevance
“…The PB1 domain has been shown previously to self-associate (forming homo-oligomers) in yeast two-hybrid studies. 37 Consistent with a previous structural characterization of TFG, 38 we found that the wild-type PB1 domain, at concentrations ranging from 18-45 μM, formed octamers in solution (~92 kD). In contrast, the c.64C4T (p. (Arg22Trp)) mutant of the PB1 domain exhibited a significantly reduced molecular mass of~24 kD (around one-fourth of the wild-type protein mass) throughout the same range of protein concentrations, indicating it was only capable of forming dimers rather than octamers.…”
Section: Biochemical Impact Of the Novel Tfg C64c4t Variantsupporting
confidence: 91%
“…The PB1 domain has been shown previously to self-associate (forming homo-oligomers) in yeast two-hybrid studies. 37 Consistent with a previous structural characterization of TFG, 38 we found that the wild-type PB1 domain, at concentrations ranging from 18-45 μM, formed octamers in solution (~92 kD). In contrast, the c.64C4T (p. (Arg22Trp)) mutant of the PB1 domain exhibited a significantly reduced molecular mass of~24 kD (around one-fourth of the wild-type protein mass) throughout the same range of protein concentrations, indicating it was only capable of forming dimers rather than octamers.…”
Section: Biochemical Impact Of the Novel Tfg C64c4t Variantsupporting
confidence: 91%
“…The N-terminal Phox and Bem1 (PB1) domain (aa 20-102) is necessary for p62/SQSTM1 to oligomerize and to interact with other PB1-containing proteins (Lamark et al 2003). Through the PB1 domain, p62/ SQSTM1 associates with several kinases, like atypical protein kinase C (aPKC) and p56 lck , and participates in signal transduction cascades (Joung et al 1996;Sanchez et al 1998).…”
Section: Structurementioning
confidence: 99%
“…p62 homo-oligomerizes through the self-interaction of its PB1 domain (Lamark et al, 2003;Wilson et al, 2003). Although NBR1 also possesses a PB1 domain (through which it interacts with p62), it instead forms homo-oligomers via its coiled-coil domain (CC1) .…”
Section: P62 Increases the Efficiency Of Nbr1-mediated Pexophagymentioning
confidence: 99%